Characterization of a xylitol dehydrogenase from Aspergillus flavus and its application in l-xylulose production - Kumar, Anurag; Li, Jinglin; Kondaveeti, Sanath; Singh, Bakul; Shanmugam, Ramasamy; Kalia, Vipin Chandra; Kim, In-Won; Lee, Jung-Kul (Frontiers in Bioengineering and Biotechnology, 2022)
An NAD+-dependent xylitol dehydrogenase from Aspergillus flavus (AfXDH) was cloned and successfully overexpressed in Escherichia coli. DNA sequence analysis revealed an open reading frame of 1,110 bp, encoding a polypeptide of 369 amino acids with a calculated molecular mass of 38,893 Da. The molecular mass of the purified enzyme (AfXDH) was estimated to be approximately 39 kDa by SDS-PAGE. Among various polyols, sorbitol and xylitol were preferred substrates of AfXDH with Km values of 16.2 mM and 16.9 mM, respectively. AfXDH showed the highest activity in Tris-glycine-NaOH buffer (pH 9.5) at 50°C; it required a divalent metal ion, either Zn2+ or Mn2+, for enzyme activity. Heat inactivation studies revealed a half-life of 200 min at 40°C and a half denaturation temperature (T1/2) of 45°C. Homology modeling and sequence analysis, along with biochemical properties, confirmed that AfXDH belonged to the medium-chain dehydrogenase/reductase family. Although XDHs have been characterized from several sources, AfXDH is distinguished from other XDHs by its high thermostability and kcat values. The feasibility of using AfXDH in L-xylulose production was demonstrated. AfXDH, when coupled with Streptococcus pyogenes NADH oxidase, efficiently converted xylitol to L-xylulose with 97% yield, suggesting its usefulness for the industrial production of L-xylulose from xylitol.